Characteristics of Pulmonary Tuberculosis Patients in RSUD Prof. DR. W. Z. Johannes Kupang - Evelyn Danielle Wijaya; Minarni Wartiningsih (Faculty of Medicine, Public Health, and Nursing, 2021)
Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis and contributes to one of the top 10 causes of death in the world. Tuberculosis sufferers in Indonesia are ranked as the 2nd most in the world. Tuberculosis cases in the province of East Nusa Tenggara continue to increase from year to year, especially in the Kupang city. Data of inpatient pulmonary tuberculosis patients in RSUD Prof. Hospital DR. W.Z. Johannes Kupang from 2017 to 2018 increased with 238 cases to 275 cases. This study aims to determine the characteristics of pulmonary tuberculosis patients hospitalized in RSUD Prof. DR. W.Z. Johannes Kupang. This research was conducted using the descriptive observational methods. Data collected using medical records with purposive sampling obtained a sample size of 51. The results of the study and conclusions showed that the majority of pulmonary tuberculosis patients hospitalized in RSUD Prof. DR. W.Z. Johannes Kupang consist of 60.8% of the male sex, 35.3% of the 45-55 year age group, 35.3% of primary school education status, and 54.9% of AFB smear-positive sputum.